The development of triploid apple cultivars is a priority in breeding - E. N. Sedov; G. A. Sedysheva; M. A. Makarkina; Z. M. Serova (Вавиловский журнал генетики и селекции, 2017)
Great attention is paid to preliminary breeding (prebreeding) when developing triploid apple cultivars. Brief characteristics of diploid gamete donors are given. It should be noted that sometimes donors of diploid gametes with necessary important traits not only have to be selected from among existing tetraploid cultivars, but also developed by a breeding way, especially in the case when in nature there are no cultivars and genotypes (donors of diploid gametes) with given traits. The authors of the paper developed form 30-47-88 (Liberty×13-6-106) by a breeding way. 30-47-88 is a complex donor of diploid gametes and scab immunity (Vf ) at once. During 1970–2015, the following work was done in apple breeding using polyploidy: 455 crossing combinations were performed; 660000 flowers were artificially pollinated; 124700 hybrid seeds were obtained and 47900 one-year-old seedlings were grown, from which after multiple rejections 13200 seedlings were planted in breeding orchards. For the first time in Russia ten apple cultivars (Avgusta, Aleksandr Boiko, Bezhin Lug, Vavilovskoye, Dariona, Maslovskoye, Orlovsky Partizan, Osipovskoye, Patriot and Yablochny Spas) have been developed from intervalence crossings and regionalized. It has been stated that apple cultivars developed at the VNIISPK are characterized, as a rule, by high productivity, better fruit marketability, greater resistance to scab and higher autogamy. Apple cultivars combining triploidy and scab immunity have been developed. Promising breeding is being performed for apple cultivars combining triploidy, scab immunity and columnar habit (Co). Brief characteristics of triploid and scab immune cultivars Vavilovskoye and Yablochny Spas developed from the intervalence crossings as well as three triploid cultivars obtained from crossings of diploid cultivars are given. It is noted that triploid apple cultivars developed at the VNIISPK are inferior to none of foreign cultivars in a complex of commercial traits and they significantly excel foreign cultivars in adaptability. Our apple cultivars may contribute to import substitution of fruit production in the country.